Re-thinking email richness and impact in institutionalcommunication from Media Richness Theory - Oliva, Carla (2025)
In today’s digital age, email has maintained its relevance as a means of institutional communication despite the emergence of more advanced technologies. This articlecritically reviews its role under the framework of Daft and Lengel’s (1986) Media Richness Theory (MRT), which initially classified email as a channel of low informationrichness. It is demonstrated how technological evolution, the massification of access to and use of this medium, has transformed its role, challenging the initial MRT classification. It is argued that email has increased its communicative richness thanks to features such as multimodal capacity, immediacy, and message personalisation. Through a comparative theoretical analysis, its flexibility, low cost, archiving capacityand reliability are highlighted as advantages over face-to-face communication. However, it also addresses the associated disadvantages, such as information overloadand the possibility of misunderstanding. The article concludes that there is a need to rethink the impact of email in contemporary institutional contexts, suggesting lines of future research to explore its evolution and communicative effectiveness further.